1985
DOI: 10.1093/ajcn/42.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fluoride intake of 6-month and 2-year-old children in four dietary regions of the United States

Abstract: Based upon the analysis of 44 market basket food collections, the average daily dietary fluoride intakes of 6-mo-old and 2-yr-old children residing in cities with water fluoride levels of 0.05 to 1.04 ppm were determined. In cities with greater than 0.7 ppm fluoride in the drinking water, a 6-mo-old child (infant) and a 2-yr-old child (toddler) had mean dietary fluoride intakes of 0.418 mg/day (0.052 mg/kg body weight) and 0.621 mg/day (0.050 mg/kg body weight) respectively. The data indicate that the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
5

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 13 publications
1
46
1
5
Order By: Relevance
“…In addition, these children ingested 0.021 mg F/kg body weight per day from fluoride toothpaste, if they brushed their teeth thrice a day. Thus, the fluoride intake from diet and tooth paste ingestion could reach the optimum value of 0.05-0.07 mg F/kg body weight per day recommended by Ophaug et al 21 and suggested to be the upper limit of daily fluoride intake by Burt. 22 This further underscores the need for comprehensive studies of fluoride exposure in a community before recommending the use of fluoride supplement or determining the appropriate fluoride level in drinking water for a community.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, these children ingested 0.021 mg F/kg body weight per day from fluoride toothpaste, if they brushed their teeth thrice a day. Thus, the fluoride intake from diet and tooth paste ingestion could reach the optimum value of 0.05-0.07 mg F/kg body weight per day recommended by Ophaug et al 21 and suggested to be the upper limit of daily fluoride intake by Burt. 22 This further underscores the need for comprehensive studies of fluoride exposure in a community before recommending the use of fluoride supplement or determining the appropriate fluoride level in drinking water for a community.…”
Section: Discussionmentioning
confidence: 98%
“…This is also a critical time for ensuring that the optimal levels of ingested fluoride are not exceeded. Several previous studies have determined the fluoride content of children foods, such as milk 1,3,14,15,26,30 , dinners and desserts 6,12,21,22,25,31 and beverages 1,13,16 . However, these studies have been limited mainly to products manufactured in North America.…”
Section: Introductionmentioning
confidence: 99%
“…It is also generally agreed that to avoid an undesirable degree of dental and skeletal fluorosis (American Academy ofPediatrics,1986) the total daily fluoride intake should not exceed 0.1 mg F/kg of body weight. Research into the total fluoride intake of infants and young children indicates that the suggested optimal levels of intake can be exceeded when there are multiple sources of fluoride (Wiatrowski it al., 1975;Adair and Wei,1978;Ophaug et al, 1985;Hattab and Wei,1988). It is therefore very important to assess the total fluoride intake of various age groups of children so that the daily fluoride intake from all sources (dietary and non-dietary) does not exceed the recommended optimal amount.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the fluoride intake of infants and young children have been based either on the analysis of commonly consumed individual food items, with or without drinking water included (Wiatrowski et al, 1975;Adair and Wei,1978;Hattab and Wei,1988), composite food items , market-basket collections (Ophaug et al, 1985;Pickston et al, 1985), hospital diets (Kramer et al, 1974), portions of cooked or uncooked foods (Nanda et al, 1974), or on "phantom meals" calculated from standard tables (McClure, 1949). Estimates of the quantity of each food consumed have also varied.…”
mentioning
confidence: 99%